2017
DOI: 10.3390/ijgi6100302
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Refugee Migration Patterns Using Geo-tagged Tweets

Abstract: Abstract:Over the past few years, analysts have begun to materialize the "Citizen as Sensors" principle by analyzing human movements, trends and opinions, as well as the occurrence of events from tweets. This study aims to use geo-tagged tweets to identify and visualize refugee migration patterns from the Middle East and Northern Africa to Europe during the initial surge of refugees aiming for Europe in 2015, which was caused by war and political and economic instability in those regions. The focus of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
(58 reference statements)
0
23
0
Order By: Relevance
“…This is the case of [28] in which the authors employ georeferenced data for about 62,000 individuals to estimate a set of US internal migration flows. Again, in [29], researchers analyze the behavior of migrants from the Middle East and Northern Africa to Europe by considering their collective mobility and its evolution in time. They highlight that one of the main problems in their study is the scarcity of geo-tagged tweets, resulting in difficulties in unfolding refugees' spatiotemporal patterns.…”
Section: Related Workmentioning
confidence: 99%
“…This is the case of [28] in which the authors employ georeferenced data for about 62,000 individuals to estimate a set of US internal migration flows. Again, in [29], researchers analyze the behavior of migrants from the Middle East and Northern Africa to Europe by considering their collective mobility and its evolution in time. They highlight that one of the main problems in their study is the scarcity of geo-tagged tweets, resulting in difficulties in unfolding refugees' spatiotemporal patterns.…”
Section: Related Workmentioning
confidence: 99%
“…Results were generally verified with travel surveys or census data [9,32], and it was concluded that working and commercially related tweets or topics gave a better estimate. For long-term and even larger spatial scale movement patterns, analysis around migration was explored, such as that in [33,34]. Although significantly limited by the sample size of valid tweets, long-term historical tweets data is still useful for exploratory analysis and inferring trends.…”
Section: Related Work-mining Spatial Patterns From Geo-tweetsmentioning
confidence: 99%
“…This condition is marked by the Makassar City development center zone as the core city connected with Maros City, Sungguminasa City and Takalar City which continue to grow and their influence on the surrounding urban suburbs. The structure of urban agglomeration space has been considered important factors affecting regional functions and sustainable development [29].…”
Section: Introductionmentioning
confidence: 99%